2020
DOI: 10.1186/s12874-020-01094-9
|View full text |Cite
|
Sign up to set email alerts
|

Protocol registration issues of systematic review and meta-analysis studies: a survey of global researchers

Abstract: Background: Although protocol registration of systematic reviews/meta-analysis (SR/MA) is still not mandatory, it is highly recommended that authors publish their SR/MA protocols prior to submitting their manuscripts for publication as recommended by the Cochrane guidelines for conducting SR/MAs. our aim was to assess the awareness, obstacles, and opinions of SR/MA authors about the protocol registration process. Methods: A cross-sectional survey study included the authors who published SR/MAs during the perio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 39 publications
4
48
3
Order By: Relevance
“…Even though this systematic review and metaanalysis has not been prospectively registered, we acknowledge that prospective registration of systematic reviews is now recommended since it promotes transparency, reduces potential for bias and avoids duplication of reviews. 56 Although there more than 60 peer-reviewed published studies (both case-control and prevalence studies) assessing the link between SIBO and IBS and IBD, less than half have measured both, methane and hydrogen on breath testing. It is now well acknowledged that lack of measurement of methane on routine breath testing could underestimate SIBO prevalence in various gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this systematic review and metaanalysis has not been prospectively registered, we acknowledge that prospective registration of systematic reviews is now recommended since it promotes transparency, reduces potential for bias and avoids duplication of reviews. 56 Although there more than 60 peer-reviewed published studies (both case-control and prevalence studies) assessing the link between SIBO and IBS and IBD, less than half have measured both, methane and hydrogen on breath testing. It is now well acknowledged that lack of measurement of methane on routine breath testing could underestimate SIBO prevalence in various gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this systematic review and meta-analysis has not been prospectively registered, we acknowledge that prospective registration of systematic reviews is now recommended since it promotes transparency, reduces potential for bias and avoids duplication of reviews. 56 …”
Section: Discussionmentioning
confidence: 99%
“…Among the SRs published in high-impact factor journals, 21.0% protocols were registered, with registered rates increasing from 5.6% in 2009 to 27.0% in 2015 ( 22 ). In the recent study, only 10.1% authors who conduct SRs completed all of their protocol registrations, while half of them never registered ( 23 ). These results confirm a universal pattern of low registered rates of SRs.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm a universal pattern of low registered rates of SRs. It's reported that this phenomenon may be due to a lack of understanding of the importance of registration and the fear of idea being stolen ( 23 ). Therefore, more efforts are needed to promote protocol registration in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Third, only RCTs and CCTs, which are regarded as the highest level of evidence, were included in our quantitative analysis [ 109 ]. Moreover, prior protocol registration and subgroup analysis were also the strengths of the current meta-analysis [ 110 , 111 ]. Different root canal area, irrigation protocols, or intracanal medicament periods are potential factors affecting the heterogeneity.…”
Section: Discussionmentioning
confidence: 99%